Heterogeneity of farms entering export supply chains: the case of fruit growers from central-south Chile - Barrena Ruiz, J. A.; Nahuelhual Muñoz, L. A.; Engler Palma, A.; Echeverría Pezoa, R.; Cofré Bravo, G. (Spanish Journal of Agricultural Research, 2013)
The increasing stringency of world food markets requires farmers to adjust farm structure and commercial strategies to remain integrated in export supply chains. The goal of this study was to identify and characterize different types of fresh fruit farms with regard to farm structural and commercial strategies for a representative sample of fresh fruit growers from central-south Chile exporting to world markets. A typology of farms was constructed based on multivariate analysis, according to which five types of farms were differentiated from five distinct factors. Cluster I comprised the smallest and uncertified farms (14.3% of the sample). The remaining four clusters comprised certified farms, but with different farm structural and commercial characteristics. Cluster II (15.1%) was composed of farms located further from market connections. Cluster III (23.9%) comprised farms with the highest number of fruit species, and consequently, more diversified in fruit production. Cluster IV (8.8%) was the smallest group, and comprised the largest firms. Finally, Cluster V (37.8%) was composed of highly specialized fruit farms, with the highest proportion of hectares dedicated to the production of a single fruit species. The results show the heterogeneity among fresh fruit farms and support the need for differentiated incentives and technological transfer schemes from the public sector and fruit companies in order to successfully keep farmers within export supply chains.